Time to Upgrade: A New OpenSPIM Guide to Build and Operate Advanced OpenSPIM Configurations. Issue 4 (10th November 2021) - Girstmair, Johannes; Moon, HongKee; Brillard, Charlène; Haase, Robert; Tomancak, Pavel
Abstract: OpenSPIM is an Open Access platform for Selective Plane Illumination Microscopy (SPIM) and allows hundreds of laboratories around the world to generate and process light‐sheet data in a cost‐effective way due to open‐source hardware and software. While setting up a basic OpenSPIM configuration can be achieved expeditiously, correctly assembling and operating more complex OpenSPIM configurations can be challenging for routine standard OpenSPIM users. Detailed instructions on how to equip an OpenSPIM with two illumination sides and two detection axes (X‐OpenSPIM) are provided, and a solution is also provided on how the temperature can be controlled in the sample chamber. Additionally, it is demonstrated how to operate it by implementing an ArduinoUNO microcontroller and introducing μOpenSPIM, a new software plugin for OpenSPIM, to facilitate image acquisition. The new software works on any OpenSPIM configuration comes with drift correction functionality, on‐the‐fly image processing, and gives users more options in the way time‐lapse movies are initially set up and saved. Step‐by‐step guides are also provided within the Supporting Information and on the website on how to align the lasers, configure the hardware, and acquire images using μOpenSPIM. With this, current OpenSPIM users are empowered in various ways, and newcomers striving to use more advanced OpenSPIM systems are helped. Abstract : New instructions and guides on how to assemble, configure, and align an X‐OpenSPIM, together with a completely overhauled software plugin (μOpenSPIM), make it easier and less time‐consuming for OpenSPIM users to upgrade to a more advanced OpenSPIM system and use it as a powerful research tool in their laboratories.